Motivational marketing : - Imbriale, Robert (John Wiley & Sons, 2007)
Every businessperson, sales professional, advertising copywriter should be endlessly exploring this question. Sadly, few do. Instead, most stay stubbornly focused on the question of: how can we make them buy our 'thing'? And, sadly, most training remains focused on selling. We are all better served pondering the psychology of the buyer ratherthan the techniques and tactics of selling. That's what Robert Imbriale has done in Motivational Marketing. This book is a valuable exercise in being about the customer